The Influence of Accountability and Sharia Principles on the Management of Village Revenue and Expenditure Budgets (APBDes) in Puger District, Jember Regency - Mamik Mutammima; Wafiq Nadia Ulfa (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2026)
Accountability in APBDes management is an important factor that determines transparency and public trust in village fund management. Sharia principles, which include justice, honesty, and responsibility, also play a role in ensuring village financial management runs in accordance with religious values and ethics. This research is a type of primary data quantitative research with purposive sampling technique. The sample used was 6 villages in Puger District, Jember Regency with 60 respondents. The data analysis method was processed using SPSS 25. The results of this study indicate that: (1) Accountability has a positive and significant effect on the management of APBDes in Puger District, Jember Regency. (2) Sharia principles have a positive and significant effect on the management of APBDes in Puger District, Jember Regency. Together, accountability and sharia principles influence the management of APBDes by 37.8%.